Water bodies of district Anantnag of Kashmir valley, their Role and Challenges: A Field Study - Misara jan; Safiya Gul; Nazakat Hashim; Arbeena Manzoor; Sadaf Rashid; Rabiya Rasool Mir; Aqsa Hanief; Daima Salim; Arshi Rafiq; Bilal Ahmad Bhat (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Kashmir, popularly known as paradise on earth is gifted with numerous water bodies comprising of rivers, lakes, streams and springs. We discuss in this paper various water bodies of district Anantnag of Kashmir valley, their present status and role. Data was collected from published resources, internet and field surveys for this study. It was found that once clean water bodies of district Anantnag like Tulian lake, Sheshnag Lake, Marsar Lake, Harbagwan Lake, Jhelum etc are at present facing significant challenges related to pollution and degradation. . The district is also home to several rivers like the Brengi, Sandran and the Lidder, which originates from Sheshnag Lake. Additionally, Verinag, a spring of historical and scenic importance, is located in Anantnag district, have fallen victim to extensive encroachment, garbage dumping, climate change, over-extraction of ground water, and the release of untreated sewage. Water bodies play a vital role in the region's ecosystem, human settlements, support local ecosystems, agriculture sector, fisheries, and tourism which play a significant role in Jammu and Kashmir’s economy. Field survey revealed that several water bodies, river banks of district Anantnag due to lack of awareness about waste management, have become dumping sites for garbage, resulting in environmental degradation as well as health hazards. Water Pollution, Siltation and Deforestation, Climate Change are the main challenges water bodies are facing in district Anantnag. In major religions of the world water is considered sacred. In Islam water occupies a pivotal role, mentioned 63 times in Quran and is recognized as a blessing that gives and sustains life, and purifies humankind and the earth. The principle of water conservation in Islam is beautifully illustrated by the rule which says that while making ablutions (wudu) we should be abstemious in the use of water even if we have a river at our disposal. In conclusion, it is the responsibility of all stake holders to protect water bodies used as drinking water sources, an important component of our lives.